(untitled) (Cadernos de Sociomuseologia, 2024)
This article is derived from my doctoral dissertation, ‘Sociomuseology at the Historical Museum Frankfurt: Cinema, Participation, and Empowerment’. It presents the fieldwork and analysis of the projects carried out, drawing inspiration from the institution’s existing participatory format – the Stadtlabor (Citylab) – as well as Brazilian museological experiences, theories, and praxis of Sociomuseology, and employing film production aspects on different levels. The development of three action-research processes aimed to provide a platform for participants to create their films with the museum, approaching topics such as the city, gender issues, and migration. The art of cinema provided a creative tool for the conception and execution of these participating musealization projects, termed ‘cinemuseological imagination’. Paulo Freire’s Methodologies of Education and Democratic Participation, along with Theories of Empowerment and Intersectionality, outlined strategies and identified the impacts on those involved. Therefore, selected elements of the research indicate some of its main findings to contribute to the comprehension of how artistic practices can envision the museum as a place for education, creativity, and empowerment. Keywords: Sociomuseology; Empowerment; Participation; Cinema; Historical Museum Frankfurt.